“A Spiritual Portrait of a Believer” : a comparison between the emphatic “I” of Romans 7, Wesley and the Mystics - Steyn, Gert (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2007.